Playfulness as a Relevant Lexeme in the Bilingual Linguistic Consciousness of Ukrainian People - Sypko, Artem; Hordiyenko-Mytrofanova, Iya (East European Journal of Psycholinguistics, 2015)
The article describes the results of the free association experiment with the stimulus word “playfulness”. The total number of respondents amounted to 3,300 people. The analysis of the associations convincingly proved that in terms of its functioning “playfulness” is a relevant lexeme in the bilingual linguistic consciousness of Ukrainian people. The further step of the research was aimed at revealing common and specific features of respondents representing different “profession types”: “person-nature”, “person-person”, “person-sign systems”, “person-technology”, “person-artistic image”. The sample involved 500 people, with 100 people for each “profession type”, men and women being equally represented. The overall number of reactions amounted to 2,452 (including word combinations and sentences (88)), with 270 occurring more than once, and 503 singular reactions. The analysis of the most frequent reactions revealed certain common features in the verbal behavior of the respondents, reflected in the lexemes “merry-making” (96(3.915)), “delight” (80(3.262)), “flirting” (79(3.221)), “laughter” (70(2.855)), “champagne” (49(1.998)), “a young girl” (46(1.876)), “children” (43(1.754)), “mood” (42(1.713)), “coquetry” (37(1.509)), “happiness” (31(1.264)), “smile” (30 (1.223%)). The analysis of singular reactions revealed the impact of professional activity on the understanding of playfulness. The procedures of sememic attribution and semic interpretation made it possible to outline the meanings of the lexeme “playfulness” and formulate their definitions as a coherent enumeration of the identified semantic components.ReferencesGordienko-Mitrofanova, I. V. (2014). Psikhologicheskaya interpretatsiya leksikograficheskogo opisaniya slova «igrivyy» [Psychological interpretation of lexicographic description ofthe word «playfulness»]. Problemy Suchasnoyi Psikhologії, 25, 83–98.Gordienko-Mitrofanova, I. V. (2014). Leksikograficheskoe znachenie slova «igrivost'»(podgotovitel'nyy etap psikholingvisticheskogo eksperimenta) [Lexicographic meaning of the word«playfulness» (preparatory stage of the psycholinguistic experiment)]. Psyhologichni PerspektyvyPsikholohіyi, 24, 76–88.Csikszentmihalyi, M. (1975). Play and intrinsic rewards. Journal of HumanisticPsychology, 15, 41–63.Bowman, J.R. (1987). Making work play. In: Meaningful Play, Playful Meanings (pp. 61–71). G.A. Fine (ed.). Champaign, IL: Human Kinetics.Glynn, M.A., & Webster, J. (1993). Refining the nomological net of the Adult PlayfulnessScale: personality, motivational and attitudinal correlates for highly intelligent adults. PsychologicalReports, 72, 1023–1026.Amabile, T.M., Hill, K.G., Hennessey, B.A., Tighe, E.M. (1994). The Work PreferenceInventory: Assessing intrinsic and extrinsic motivational orientations. Journal of Personality andSocial Psychology, 66(5), 950–967.Tsuji, Hit., Tsuji, Hei., Yamada, S., Natsuno, Y., Morita, Y., Mukoyama, Y., Hata, K.,Fujishima, Y. (1996). Standardization of the Five Factor Personality Questionnaire: Factor structure.International Journal of Psychology, 31, 103–217.Bozionelos, N., & Bozionelos, G. (1997). Psychology of computer use: XLVIII: Relationbetween playfulness and computer anxiety. Psychological Reports, 81, 956–958.Dunn, L. L. S. (2004) Cognitive playfulness, innovativeness, and belief of essentialness:Characteristics of educators who have the ability to make enduring changes in the integration oftechnology into the classroom environment. Ph.D. dissertation. Retrieved from:http://digital.library.unt.edu/ark%3A/67531/metadc4620/Yu, P., Wu, J-J., Chen, I., Lin, Y.T. (2007). Is playfulness a benefit to work? Empiricalevidence of professionals in Taiwan. International Journal of Technology Measurement, 39(3/4),412–429.Tan, J. P-L. (2009) Digital kids, analogue students: A mixed methods study ofstudents’ engagement with a school-based Web 2.0 learning innovation. (Unpublished doctoraldissertation.) Centre for Learning Innovation, Faculty of Education Queensland University ofTechnology, Australia.Proyer, R.T. (2011). Being playful and smart? The relations of adult playfulness withpsychometric and self-estimated intelligence and academic performance. Learning and IndividualDifferences, 21, 463–467.Proyer, R.T., Ruch W. (2011). The virtuousness of adult playfulness: the relation ofplayfulness with strengths of character, Psychology of Well-Being: Theory, Research and Practice,1, 4.Tan J., McWilliam E.(2013) Cognitive playfulness, creative capacity and generation.Lifelong education: the XXI century, 2, 1–9. doi: 10.15393/j5.art.2013.2090.Huizinga, J. (2003). Homo Ludens, Moscow: Ayris-press.Gordienko-Mytrofanova, I., Sypko, A. O., Sukhan, V. A. The influence of gender, ageand profession-related differences on the verbal behavior of the subjects of association. Retrieved:01.03.2015 from http: // fund-issled-intern.esrae.ru/5-63.Ufimtseva, N. V. (2006) Psikholingvistika i mezhkul’turnaya kommunikatsiya[Psycholinguistics and cross-cultural communication]. Rechevaya deyatel’nost’. YazykovoeSoznanie. Obshchayushchiesya Lichnosti. Moscow; Kaluga: Eydos.Klimov, E.A. (2004). Psikhologiya professional'nogo samoopredeleniya [Professionalself-determination in psychology], Moscow: Akademiya.Meshherjakov, B., Zinchenko, V. Vosprijatie [Perception]. In: Bol'shoj psihologicheskijslovar' [Big Psychology Dictionary]. Retrieved: 01.03.2015 fromhttp://www.gumer.info/bibliotek_Buks/Psihol/dict/03.php.